2017
DOI: 10.1038/s41598-017-03382-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of the Regulation of Lipid Fraction Migration and Fatty Acid Biosynthesis in Schizochytrium sp.

Abstract: Schizochytrium sp. is the main source of docosahexaenoic acid-rich oil, which is widely used in food additive and pharmaceutical industry. In this study, using RNA-seq, comparative transcriptomic analyses were performed at four stages of DHA fermentation by Schizochytrium sp to get potential genes related to cell transition from cell growth to lipid accumulation and then to lipid turnover. 1406, 385, 1384 differently expressed genes were identified by comparisons in pairs of S2 vs S1, S3 vs S2 and S4 vs S3. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…ATCC20888 without the present of -12 desaturation. Ren et al (2017), detected one elongase and three kinds ( -6, -8, and -12) of desaturase activities in Schizochytrium sp. The missing of some specific enzymes might be the reason of the incomplete genomic information.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…ATCC20888 without the present of -12 desaturation. Ren et al (2017), detected one elongase and three kinds ( -6, -8, and -12) of desaturase activities in Schizochytrium sp. The missing of some specific enzymes might be the reason of the incomplete genomic information.…”
Section: Discussionmentioning
confidence: 95%
“…ATCC20888 without the present of -12 desaturation. Ren et al (2017), detected one elongase and three kinds ( -6, -8, and -12) of desaturase activities in Schizochytrium sp. PKS pathway of LC-PUFAs synthesis involve the processing of the saturated 16:0 or 18:0 products by repetitive decarboxylative Claisen ester condensations.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, we identified three genes associated with the PKS route of PUFAs biosynthesis—ORFA, ORFB, and ORFC. During the cell growth stage, all genes involved in the PKS pathway showed high expression levels [ 26 ]. Our transcription results showed that PKS genes (ORFA, ORFB, and ORFC), which are directly involved in the DHA biosynthesis, were significantly differentially expressed between normal and high oxygen supply conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Among the three genes encoding PKS enzymes, ORFC expression was increased the most, and was 4.12- and 3.34-fold higher than that of the parental strain at 60 and 180 h, respectively. ORFC contains two DH (dehydrase) domains and one ER (enoyl-ACP reductase) domain, which showed higher sensitivity to the changes of environmental factors [ 61 ]. DH catalyzes the conversion of ketoacyl-ACP to enoyl-ACP, and the ER domain catalyzes the final step of fatty acid chain extension in which it reduces the double bond.…”
Section: Discussionmentioning
confidence: 99%